Clinical Study on Prevention of Irinotecan-Induced Delayed-Onset Diarrhea by Hot Ironing with Moxa Salt Packet on Tianshu and Shangjuxu - Xianghong Lai; Anmei Wang (Emergency Medicine International)
Objective. To study the clinical efficacy of hot ironing of the Tianshu and Shangjuxu with moxa salt packet to prevent irinotecan (CPT-11)-induced delayed-onset diarrhea (IIDD). Methods. A randomized controlled study was conducted on a sample of 120 patients with advanced colorectal cancer who were hospitalized in our oncology department and treated with FOLFIRI chemotherapy regimen from February 2018 to July 2021. They were equally divided into study group (n = 60) and control group (n = 60) according to whether they were treated with hot ironing with moxa salt packs or not. The general conditions, occurrence of IIDD, occurrence of delayed chemotherapy due to IIDD, time of occurrence and duration of IIDD, Karnofsky performance score (KPS) score, occurrence of leukopenia, and myelosuppression were compared between the two groups. Result. The incidence of grade 1, 2, 3, and 4 diarrhea in the study group was 11.67% (7/60), 5.00% (3/60), 3.33% (2/60), and 0.00% (0/60), respectively, while the incidence of grade 1, 2, 3, and 4 diarrhea in the control group was 21.67% (13/60), 8.33% (5/60), 10.00% (6/60), and 3.33% (2/60). The incidence of severe diarrhea and total diarrhea in the study group was (3.33% and 20.00%) lower than that in the control group (13.33% and 43.33%) (P<0.05). The incidence of delayed chemotherapy was lower in the study group (8.33%) (1/12) than in the control group (23.08%) (6/26) but the difference between the groups was not statistically significant (P>0.05). The time to onset of IIDD in the study group (6.45 ± 1.53) days was comparable to that in the control group (6.40 ± 1.77 days) (P>0.05), but the duration of IIDD in the study group (3.25 ± 1.05 days) was shorter than that in the control group (5.70 ± 1.72 days) (P<0.05). After treatment, the incidence of KPS improvement, stabilization, and reduction in the study group was 38.33% (23/60), 51.67% (31/60), and 10.00% (6/60), respectively, the incidence of KPS improvement, stabilization, and reduction in the control group was 23.33% (14/60), 50.00% (30/60), and 26.67% (16/60), respectively, and the percentage of KPS reduction in the study group was less than that in the control group (P<0.05). During the observation period after treatment, the total incidence of leucopenia in the study group was 11.67% (7/60) which is lower than 31.67% (19/60) in the control group (P<0.05). During the observation period after treatment, the incidence of III°+°IV myelosuppression in the study group was 5.00% (3/60) which is lower than 25.00% (15/60) in the control group (P<0.05). Conclusion. The hot ironing with moxa salt packet on Tianshu and Shangjuxu was more effective in preventing IIDD, which could reduce the incidence and severity of IIDD, shorten the duration of diarrhea and significantly increase the quality of life of patients with no significant adverse effects.